The perception of mobile payment systems and measuring the effects of digital nudging - Evcil, Melike. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
This thesis is a study on the perception of mobile payment systems and measuring the effects of digital nudging techniques. The thesis aims to explore the relationships between risk perception, mobile payment systems usage, trust in mobile payments, positive and negative factors for mobile payment systems. Furthermore, in the second part of the study, it has been investigated whether trust in mobile payments and mobile payment systems usage differ according to different digital nudging techniques. Two different online surveys were conducted with 241 university students in Turkey with each student filling out one type of the surveys. In the first part of the survey, the questions were the same, while in the second part, the questions changed and different digital nudging techniques were applied. According to the results of both studies, significant positive relationships were found between risk perception and mobile payment systems usage, risk perception and trust in mobile payments, mobile payment systems usage and trust in mobile payments, mobile payment systems usage and positive factors for mobile payment systems. In the second part, it was found that mobile payment usage and trust in mobile payments differ significantly according to different digital nudging techniques. It was found that trust in mobile payments differs according to different informative data, mobile payment usage differs according to positive data, trust in mobile payments and mobile payment usage differ according to a case, mobile payment usage differs according to the structure and the priority of answers.
Keywords: Mobile commerce.